Enhanced sintering resistance of Fe2O3/CeO2 oxygen carrier for chemical looping hydrogen generation using core-shell structure. (8th March 2019) - Ma, Shiwei; Chen, Shiyi; Zhu, Min; Zhao, Zhenghao; Hu, Jun; Wu, Mudi; Toan, Sam; Xiang, Wenguo
Abstract: CeO2 -supported Fe2 O3 is a satisfactory oxygen carrier for chemical looping hydrogen generation (CLHG). However, the sintering problem restrains its further improvement on redox reactivity and stability. In the present work, a core-shell-structured Fe2 O3 /CeO2 (labeled Fe2 O3 @CeO2 ) oxygen carrier prepared by the sol-gel method was studied in a fixed bed. The effect of the core-shell structure on the sintering resistance and redox performance was investigated with a homogenous composite sample of Fe2 O3 /CeO2 as a reference. The results showed that the Fe2 O3 @CeO2 exhibited much higher redox reactivity and stability than the Fe2 O3 /CeO2 with no CO or CO2 observed in the generated hydrogen, while the hydrogen yield for Fe2 O3 /CeO2 decreased with redox cycles due to serious sintering. The satisfactory performance of Fe2 O3 @CeO2 can be ascribed to its high sintering resistance, since the core-shell structure suppressed the outward migration of Fe cations from the bulk to the surface of the particles. On the other hand, the migration of Fe cations and their subsequent enrichment on the particle surface led to the serious sintering of Fe2 O3 /CeO2 . The crystallite size evolution of Fe2 O3 and CeO2 in redox cycles further demonstrated the higher sintering resistance of Fe2 O3 @CeO2 . Further, the particle size distribution (PSD) results indicated the agglomeration of Fe2 O3 /CeO2 after cycles. In addition, the CeO2 shell could facilitate the transport of oxygen ions between the iron oxide nanoparticle core and the shell surface. Therefore, the coating of nanoscale Fe2 O3 with a CeO2 shell did not reduce the redox reactivity and stability of Fe2 O3 @CeO2, but rather promoted it, though less oxygen-ionic-conductive CeFeO3 was generated. Graphical abstract: Image 1 Highlights: A core-shell structured Fe2 O3 @CeO2 prepared by sol-gel method was studied for CLHG. Fe2 O3 @CeO2 exhibited significantly enhanced sintering resistance. Fe2 O3 @CeO2 showed much higher activity and stability than the composite Fe2 O3 /CeO2 . Fe2 O3 @CeO2 prevented the outward migration of Fe cations from the bulk to surface. CeO2 shell facilitated oxygen mobility between the Fe2 O3 core and the shell surface.